EVALUASI KETERWAKILAN 30% PEREMPUAN PADA PEMILU LEGISLATIF TAHUN 2019 DI DEWAN PERWAKILAN RAKYAT PAPUA - Yanni, Yanni; Aedah, Nur; Torobi, Renida J. (JURNAL KEBIJAKAN PUBLIK, 2024)
Women's involvement in politics continues to show an increase over time. This increase, especially in terms of women's representation in elections, is not the result of chance, but the fruit of a consistent struggle to realize equality and justice for all parties. This research aims to analyze the implementation of the 30% women's representation policy and identify the supporting and inhibiting factors in the implementation of the 2019 Legislative Elections in the Papua House of Representatives. This research is important because women's representation in politics is one indicator of the success of an inclusive and equitable democracy. The method used in this research is descriptive qualitative. The results show that the implementation of the 30% women's representation policy in the 2019 Legislative Election in the Papua House of Representatives has been achieved. However, the effectiveness of the policy in fulfilling the women's quota has not fully reflected optimal implementation. The efficiency of 30% women's representation has not been achieved because female legislative candidates still face the high need for time, money, and energy to compete. The government's responsiveness to people's demands regarding women's representation is also still limited. Policy accuracy is considered capable of identifying the problems of women legislative candidates, especially in Papua Province, but implementation efforts require improvement to be maximized. Factors supporting women's representation include equality in political positions and protection of women's interests. On the other hand, women's representation still faces obstacles stemming from limited individual abilities and strong cultural barriers.